Industrial training report: Robert Bosch Automotive Steering Sdn Bhd / Nurul Nuha Mansor - Mansor, Nurul Nuha (Universiti Teknologi MARA, Perlis, 2024)
SummaryI have prepared my internship report based on the six months long internship programthat I had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from1 September 2023 to 9 February 2024 as a requirement of my Bachelor of BusinessAdministration (HONS) Human Resource Management. Robert Bosch AutomotiveSteering is a company that develops, produces, and sells steering technology forpassenger cars and commercial vehicles. In addition, this report determines my goal and internship experience, beginningwith my duties and tasks as an Human Resource trainee. My duties including applyingtraining to employee who needed, monthly newsletter which in the newsletter willhave information about past event, employee birthday, monthly calendar, publicholidays and general sharing. Moreover, I also need to update monthly datadeclaration for micare and great eastern which is insurance for employee. Wheneverthere is a new family member, any death of family member or resignation, there will bean update for data declaration.I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I have prepared my internship report based on the six months long program that had successfully completed in Robert Bosch Automotive Steering Sdn. Bhd. from 1 September 2023 to 9 February 2024 as a requirement of Bachelor Business Administration (HONS) Human Resource Management. is company develops, produces, and sells steering technology for passenger cars commercial vehicles. I